Sequences necessary for nitrate-dependent transcription of Arabidopsis nitrate reductase genes. - Hwang, C F (1997)
Nitrate increases the transcription of the two Arabidopsis thaliana nitrate reductase genes. We demonstrated previously that 238 and 330 bp of the 5' flanking regions, designated as NP1 and NP2, of the two nitrate reductase genes NR1 and NR2, respectively, are sufficient for nitrate-dependent transcription (Y. Lin, C.-F. Hwang, J.B. Brown, C.-L. Cheng [1994] Plant Physiol 106: 477-484). Here we identify the cis-acting elements of NP1 and NP2 that are necessary for nitrate-dependent transcription by linker-scanning (LS) analysis. In transgenic plants one LS mutant of NP1 and two LS mutants of NP2 exhibited significantly lower nitrate-induced reporter gene chloramphenicol acetyltransferase activity. To distinguish which of these three mutants lost nitrate inducibility, competitive reverse-transcriptase polymerase chain reaction was used to measure the chloramphenicol acetyltransferase mRNA levels before and after nitrate induction. The single LS mutant in NP1 lost its response to nitrate, whereas the two LS mutants in NP2 partially lost their response to nitrate. A 12-bp sequence is conserved between the NP1 site and the two NP2 sites. This sequence motif is also conserved in the 5' flanking regions of other nitrate-inducible plant genes. Gel mobility shift experiments indicate that these three regions bind to similar proteins. The binding is constitutive with respect to nitrate treatment and was observed in both nonphotosynthetic suspension cells and green leaves.